PENGARUH PUPUK CAIR LIMBAH ORGANIK RUMAH TANGGA TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) - Aidilla Febra; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of household organic waste liquid fertilizer on the growth and production of peanutsand determine the concentration of good liquid organic fertilizer. The experiment lasted for 4 month from November 2017 to Februari 2018 experimental garden of Agricultural Faculty of Riau University. This research using a randomized block design (RDB) consisting of five treatments and four replications. The treatment given is K0 = 0 ml POC.l-1 water, K1 = 2.5 ml POC.l-1 water, K2 = 5 ml POC.l-1 water, K3 = 7.5 ml POC.l-1 water, and K4 = 10 ml POC.l-1 water. The parameters observed were plant height, age of flowering plants, harvest age, number of pods per plant, percentage of pithy pods, number of seeds per pod, dry seed weight per m2, and weight of 100 seeds. The data obtained were analyzed using Anova and Duncan on levels 5%. The results showed that household organic liquid fertilizer can affect plant height, age of flowering plant, harvest age, number of pods per plant, number of seeds per pod, dry seed weight per m2, and weight of 100 seeds. The concentration of household organic liquid fertilizer7.5 ml.l-1 water and 10 ml.l-1 water give the best results in increasing the production of peanut plants.Keywords: Peanuts, concentration, liquid organic fertilizer